Industrial waste as a factor of increasing the chemical resistance of ceramics - Lev Chernyak (Zaštita Materijala)
The possibility of the manufacturing of ceramics with equally high indicators of acid and alkali resistance is shown. The effect achieved is associated with the formation of a system of crystalline phases of anortite-hematite-cristobalite during the firing of masses created on the base of compositions of red mud and polymineral clay. Technological schemes of the production of ceramic materials from masses with the total content of 60-80% of red mud, non-ferrous metallurgy waste, which is the factor of increase of decorative and operational characteristics of production are proposed.